PERANAN PUBLIC RELATION DALAM MEMPERTAHANKAN CITRA BALI DYNASTY RESORT - Maya Kurniawati; Syofia Achnes (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The purpose of this study was to describe the shape of the role played by the Public Relations of Bali Dynasty Resort in maintaining the image of Bali Dynasty Resort. Choosing Bali as a tourist destination worldwide daily visited by many tourists at home and abroad. In her choose Bali Dynasty Resort for a Resort that was established a long time and the only the concept